Music and Noise: Same or Different? What Our Body Tells Us - Reybrouck, Mark; Podlipniak, Piotr; Welch, David (Frontiers in Psychology, 2019)
In this paper we consider music and noise in terms of vibrational and transferable energy as well as from the evolutionary significance of the hearing system of Homo Sapiens. Music and sound impinge upon our body and our mind and we can react to both either positively or negatively. Much depends, in this regard, on the frequency spectrum and the level of the sound stimuli may sometimes make it possible to set music apart from noise. There are, however, two levels of description: the physical-acoustic description of the sound as well as the subjective-psychological reactions by the listeners. Starting from a vibrational approach to sound and music, we first investigate how sound may activate the sense of touch and the vestibular system of the inner ear besides the sense of hearing. We then touch upon distinct issues such as the relation between low-frequency sounds and annoyance, the harmful effect of loud sound and noise, the direct effects of overstimulation with sound, the indirect effects of unwanted sounds as related to auditory neurology, and the widespread phenomenon of liking loud sound and music, both from the point of view of behavioural and psychological aspects.